A tabletop exercise approach to global disaster preparedness: insights from Nepal’s first international conference on disaster preparedness and management - Pandya, Jay; Kharel, Ramu; McMahon, Jonathan; Basnet, Samjhana; Soghoian, Samara; Pradhan, Binita; Arquilla, Bonnie (Frontiers in Public Health, 2024)
Considering recent earthquakes and the COVID-19 pandemic, disaster preparedness has come to the forefront of the public health agenda in Nepal. To strengthen the developing health system, many initiatives are being implemented at different levels of society to build resiliency, one of which is through training and education. The first International Conference on Disaster Preparedness and Management convened in Dhulikhel, Nepal on December 1–3, 2023. It brought together international teaching faculty to help deliver didactic and simulation-based sessions on various topics pertaining to disaster preparedness and management for over 140 Nepali healthcare professionals. This paper focuses on the tabletop exercise-based longitudinal workshop portion of the conference on disaster leadership and communication, delivered by United States-based faculty. It delves into the educational program and curriculum, delivery method, Nepali organizer and US facilitator reflections, and provides recommendations for such future conferences, and adaptation to other settings.